Analysis of post-mining land use sustainability: Analysis of post-mining land use sustainability - nindi, nindi (ReTII, 2021)
Result of mining is changes in the physical, chemical and biological properties of the soil, it is necessary to an analysis of the management of ex-mining land. One of the activities that can minimize damage is sustainable post-mining land reclamation activities. To analyze the sustainability of post-mining land, necessary of attention to land quality. Land quality consists of soil quality and water quality which area very important environmental component. Sustainability analysis can be using the Likert scale method and the rapfish technique. The Likert scale method that is most widely used in research is in the form of surveys. The scale is used to facilitate tiered measurements. The rating scale, for example, is a scale for assessing something with tiered choices, for example 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10. The Likert scale is also a tool for measuring (collecting data by means of " measuring-weighing") whose "items" (question items) contain tiered options, while the latest rapfish technique which is the development of a multidimensional scaling technique which is also carried out Leverage analysis is used to determine attributes, Monte Carlo analysis is used to estimate the effect of error in the analysis process, the Stress value and the coefficient of determination (R2) function to determine whether or not additional attributes are needed to reflect dimensions with a Stress value below 0.25 and an R2 value above 95% confidence, the quality from the MDS analysis can be accounted for. Keywords: Post-mining land, sustainable, land quality, Likert scale, rapfish technique